Penguatan Literasi Digital melalui Coding Games pada Pendidikan Nonformal Anak Pekerja Migran Indonesia - Ahmad, Nur; Supeno, Supeno; Wahyuni, Sri; Putra, Pramudya Dwi Aristya; Nuha, Ulin; Rusdianto, Rusdianto; Lesmono, Albertus Djoko; Prasetya, Ferry Budi; Amrullah, Jadnika Dwi Rakhmawan (LPPM Universitas PGRI Argopuro Jember, 2026)
The rapid development of digital technology demands the strengthening of 21st-century skills, particularly computational thinking, including in non-formal education. This article describes the implementation and outcomes of a community service program involving game-based coding learning to enhance digital literacy and computational thinking skills among children of Indonesian migrant workers at Sanggar Belajar Kampung Baru, Kuala Lumpur. The program was conducted through planning, implementation, and evaluation stages using an interactive, gradual, and collaborative visual learning approach. Evaluation was carried out qualitatively through observation, interviews, and discussions. The results indicate increased learning motivation, active participation, and initial understanding of programming logic. The game-based approach helped reduce the perception that coding is difficult and abstract, while encouraging exploration and collaboration. Furthermore, the program positively contributed to psychosocial aspects, such as self-confidence and social interaction, indicating its potential for long-term benefits for the learners.